2020
DOI: 10.1111/1541-4337.12608
|View full text |Cite
|
Sign up to set email alerts
|

Fonio grains: Physicochemical properties, nutritional potential, and food applications

Abstract: Fonio grains are a type of small-seeded cereals native to Western Africa and are important cereal crops for food security. The two species are white fonio (Digitaria exilis) (commonly called acha) and black fonio (Digitaria iburua) (commonly called iburu). As a novel food, fonio has attracted attention from other parts of the world due to their attractive nutritional properties (e.g., in whole grain form and being gluten free) and potential food applications. The information regarding the functional properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 116 publications
(336 reference statements)
0
15
0
Order By: Relevance
“…Fonio did not exhibit any foaming capacity, while millet and sorghum flours exhibited the highest FC and FS, probably due to their higher protein content. It has been reported that protein–carbohydrate interactions in fonio may contribute to the low solubility of fonio proteins [ 6 ], resulting in lower availability to interact with water and generate foam. No FS was measured in fonio, given that no foam was formed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fonio did not exhibit any foaming capacity, while millet and sorghum flours exhibited the highest FC and FS, probably due to their higher protein content. It has been reported that protein–carbohydrate interactions in fonio may contribute to the low solubility of fonio proteins [ 6 ], resulting in lower availability to interact with water and generate foam. No FS was measured in fonio, given that no foam was formed.…”
Section: Resultsmentioning
confidence: 99%
“…Despite its low agronomic yield potential, fonio is gaining importance as a crop and food ingredient due to its superior nutritional characteristics compared with other cereals, the increased market interest in traditional food, and its suitability to be grown in tough conditions, such as in arid soil. Fonio flour has been mixed with other ingredients to improve the nutritional and textural quality of different food products such as malts, beverages, sourdough, bread, puddings, crackers, breakfast cereals, and biscuits [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations